PARP Inhibitors in Ovarian Cancer: A Review - O’Malley, David M.; Krivak, Thomas C.; Kabil, Nashwa; Munley, Jiefen; Moore, Kathleen N. (Targeted oncology, 2023)
Poly(ADP-ribose) polymerase (PARP) inhibitors (PARPis) have transformed the ovarian cancer (OC) treatment landscape. This narrative review provides a comprehensive overview of data for the PARPis olaparib, niraparib, and rucaparib in patients with OC and discusses their role in disease management, with a focus on the use of PARPis as maintenance therapy in the United States (US). Olaparib was the first PARPi to be approved as first-line maintenance monotherapy in the US, with maintenance niraparib subsequently approved in the first-line setting. Data also support the efficacy of rucaparib as first-line maintenance monotherapy. PARPi maintenance combination therapy (olaparib plus bevacizumab) also provides benefit in patients with newly diagnosed advanced OC whose tumors tested positive for homologous recombination deficiency (HRD). Biomarker testing is critical in the newly diagnosed setting to identify patients most likely to benefit from PARPi maintenance therapy and guide treatment decisions. Clinical trial data support the use of PARPis (olaparib, niraparib, rucaparib) as second-line or later maintenance therapy in patients with platinum-sensitive relapsed OC. Although distinct differences in tolerability profile were observed between PARPis, they were generally well tolerated, with the majority of adverse events managed by dose modification. PARPis had no detrimental effect on patients’ health-related quality of life. Real-world data support the use of PARPis in OC, although some differences between PARPis are apparent. Data from trials investigating novel combination strategies, such as PARPis plus immune checkpoint inhibitors, are awaited with interest; the optimal sequencing of novel therapies in OC remains to be established.